The Comparison of Bone Mineral Density Between Postmenopausal Women and Elderly Women - Bülent Çakmak; Ahmet İnanır; Gökhan Tuna Öztürk (Galenos Yayinevi, 2012)
Aim: The aim of our study is comparison of bone mineral density (BMD) between postmenopausal non-geriatric (age 45-64) and elderly women (age >65). Materials and Methods: In this study, 457 postmenopausal non-elderly and 99 elderly women whom have been measured BMD at Gaziosmanpaşa University Hospital Physical Medicine and Rehabilitation outpatient clinic between January 2010 - December 2012 were received for evaluation. Two patient group were compared for age, body mass index (BMI), menopause period, value of BMD of hip and lomber spine, and presence of osteoporosis. Results: The mean age of elderly and non-elderly women was detected 70.3±5.1 and 53.9±5.4 years, respectively (p<0.001). There was no statistically significant difference between two groups when the height, weight and BMI were compared (p>0.05). Menopause period was found higher in elderly women than non-elderly (p<0.001). The value of BMD of lomber spine and hip was detected 0.86±0.17 and 0.87±0.13 g/cm2 in elderly women, and 0.93±0.13 and 0.95±0.14 g/cm2 in non-elderly women. And significant difference was found between these two groups (p<0.001). Osteoporosis was determined in 45.5% of elderly women and 20.1% of non-elderly women, and significant difference was found between the two groups (p<0.001). Conclusion: The value of BMD was detected lower in elderly women than non-elderly women, in parallel with this situation, rate of osteoporosis was found higher in elderly women. Reduction in value of BMD begins with menopause. In addition, this reduction also accelerates with the advancement of age and the effects of senility. (Turkish Journal of Osteoporosis 2012;18: 86-8)